DEFA5-producing CD4+ T cells in the intestines of atopic dermatitis patients play an important role in the development of AD-associated intestinal inflammation - Zhuang, Kai; Li, Mengjun; Wu, Yalan; Luo, Yi; Song, Jian; Chan, Sze Chun Leo; Li, Jinmei; Chen, Ziying; Ouyang, Yulin; Zhang, Yongliang; Lin, Ying; Luo, Huanhuan (Frontiers in Immunology, 2025)
RationaleAtopic dermatitis (AD) is associated with various gastrointestinal symptoms, yet the underlying mechanisms remain poorly understood. This study aimed to investigate intraepithelial lymphocytes (IELs) in the intestines of AD patients and their potential contribution to intestinal inflammation.MethodsSingle-cell RNA sequencing was utilized to analyze the immune cell composition in the ileum of adult AD patients with severe symptoms. Laser confocal microscopy, Western blot, polymerase chain reaction and adoptive T cell transfer experiments were carried out to investigate the phenotypes of IELs and contribution of CD4+ IELs in intestinal inflammation and barrier function.ResultsA distinct group of DEFA5-expressing CD4+ T cells in the small intestine of AD patients was identified. These cells were enriched in tissue resident memory T cells (Trm). Peroxisome proliferator-activated receptor (PPAR) was found to be important for the function of DEFA5-expression CD4+ IELs. In an AD mouse model, an increase in DEFA5-expressing CD4+ IELs was observed compared to control, and these cells contributed to the development of intestinal inflammation and impaired intestinal barrier function.ConclusionsAD is linked to an increase in intestinal DEFA5-expressing CD4+ IELs, which may play an important role in mediating intestinal inflammation. This suggests that the DEFA5-expressing CD4+ IELs could be a potential therapeutic target for managing gastrointestinal symptoms in AD patients.